A TRIAD OF EXCELLENCE: HOW STRATEGIC LEADERSHIP, INTELLECTUAL CAPITAL AND IT INNOVATION DRIVE COMPETITIVE ADVANTAGE IN HIGHER EDUCATION INSTITUTIONS - Sazly, Syukron; Al Rasyid, Harun; Tri Indah K, Agus (Universitas Muhammadiyah Tangerang, 2025)
This study analyzes the determinants of sustainable competitive advantage through the Resource-Based View (RBV) approach, focusing on strategic leadership, intellectual capital, and technological innovation. The qualitative method was applied through a systematic review of 27 selected literature (Scopus and nationally accredited). The results reveal: (1) strategic leadership plays a role as a guide for long-term vision, (2) intellectual capital (knowledge, skills, innovation) becomes irreplaceable assets, and (3) technological innovation increases productivity, product differentiation, and market adaptation. The interaction of the three creates a sustainable competitive ecosystem. This research contributes theoretically to the development of strategic and practical management as a business guide in the digital era. Recommendations for further research include the expansion of variables (organizational culture, business networking, dynamic capabilities) and the application of mixed methods. These findings underscore the importance of inter-factor synergy in building a competitive advantage that is resistant to disruption.